Imperfection sensitivity of externally pressurised shells: Static and pulse loading - Blachut, Jan (European Journal of Computational Mechanics, 2004)
The paper examines the sensitivity of buckling loads to the initial geometric imperfections in metallic cylindrical, toroidal, barrelled and torispherical shells subjected to uniform external pressure. The adopted approach is based on the FE analysis of a number of selected cases. The imperfection profiles include either localised (stripe, cos x cos, increasedradius flattening, etc.) or global (modulated eigenmode) distortion of shell’s mid-surface. The lower bound methodology has been adopted for all localised shape deviations. Differences between buckling sensitivities to localised and global imperfections are given for the following cases: (i) for cylinders subjected to radial pressure, (ii) for toroids and torispheres subjected to static external pressure. It is shown here that the largest reduction of the buckling strength is not associated with one particular form of shape deviations. In bowed out shells the eigen-imperfections seem to be affecting the load carrying capacity to a lesser extent than in equivalent cylinders. Dynamic failure loads of imperfect torispheres are smaller than their static ones but only for up to threshold magnitudes.References to previous buckling experiments on perfect and imperfect shell components are also provided.